Multiple Major and Minor Anomalies Associated With Klippel-Feil Syndrome: A Case Report - Nada VUJASINOVIC STUPAR,; Slavica PAVLOV-DOLIJANOVIC,; Nur HATIB,; Bojan BANKO,; Milan DJUKIC,; Natasa NIKOLIC JAKOBA, (Archives of Rheumatology, 2016)
Klippel-Feil syndrome is defined as congenital fusion of two or more cervical vertebrae. In this article, we report a 55-year-old male patient with one-year history of neck pain, headaches, and one episode of syncope after a severe trauma. X-rays and magnetic resonance imaging of cervical spine revealed fused vertebral bodies of C2-C5. The major anomalies associated with Klippel-Feil syndrome (small stature, thoracic kyphoscoliosis, lumbar scoliosis, restricted opening mouth, and bilateral sensorineural hearing loss) as well as multiple minor anomalies (mild face asymmetry, high arched palate, rhinoscoliosis, high nasal bridge, inclined septi nasi, and thin upper lip) were detected. This is a rare case describing the anomalies of the nose in Klippel-Feil syndrome patients. Our patient had no central cord impairment following a severe trauma.